2020
DOI: 10.1128/aac.00717-20
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Respiratory Syncytial Virus N 0 -P Complex with Constrained α-Helical Peptides in Cells and Mice

Abstract: RSV is the main cause of severe respiratory infection in young children worldwide for which no therapies are approved for treatment. Recent clinical trials data resulting from the treatment of RSV infected patients with fusion or L polymerase inhibitors revealed the emergence of escape mutants highlighting the need for the discovery of inhibitors with novel mechanism of action. Here we describe stapled peptides derived from the N-terminus of the phosphoprotein P that act as replication inhibitors. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
(233 reference statements)
0
9
0
Order By: Relevance
“…The latter region displays a high degree of sequence conservation ( Figure 2 ), which suggests that the transient helix observed in free RSV P can be stabilized upon complex formation ( Figure 4 ). This was further corroborated by binding assays of the RSV N -terminal P peptides, spanning residues E11–S30 and constrained into an α-helical conformation by stapling to the monomeric N. These stapled peptides competed with the equivalent wild-type peptide and furthermore exhibited antiviral activity on recombinant RSV viruses in vitro and in vivo [ 81 ].…”
Section: Folding Upon Binding In the Intrinsically Disordered Domamentioning
confidence: 83%
“…The latter region displays a high degree of sequence conservation ( Figure 2 ), which suggests that the transient helix observed in free RSV P can be stabilized upon complex formation ( Figure 4 ). This was further corroborated by binding assays of the RSV N -terminal P peptides, spanning residues E11–S30 and constrained into an α-helical conformation by stapling to the monomeric N. These stapled peptides competed with the equivalent wild-type peptide and furthermore exhibited antiviral activity on recombinant RSV viruses in vitro and in vivo [ 81 ].…”
Section: Folding Upon Binding In the Intrinsically Disordered Domamentioning
confidence: 83%
“…Accumulating data confirmed that the region encompassing residues 12-24 of P has a propensity to adopt an α-helical conformation that is stabilized upon binding [63,114,115]. Based on this observation, a strategy aiming at specifically targeting the N 0 -P interaction using dominant negative peptide inhibitors that mimic the N-terminus of P was recently developed [126]. These inhibitors were synthesized using the stapled peptide technology that constrains short peptides into α-helical conformation [127][128][129].…”
Section: The Pneumovirus N 0 -P Complexmentioning
confidence: 99%
“…Of note, such a strategy was used to design peptide inhibitors of the hRSV F protein involved in the virus entry [130,131]. Screening of stapled peptides derived from the N-terminal sequence of P allowed identification of peptides derived from residues 7-30 of P, presenting an antiviral activity in cell culture, with an EC 50 of approximately 10 µM [126]. Despite limited antiviral activity in cell cultures, the lead peptide was shown to reduce hRSV infection in vivo in a mouse model [126].…”
Section: The Pneumovirus N 0 -P Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that these peptides inhibit RSV replication in vitro and in vivo in BALB/c mice, through preventing the formation of the N 0 -P complex. [12]…”
Section: Targeting Conserved Viral Fusion and Replication Mechanisms ...mentioning
confidence: 99%